2021
DOI: 10.29303/jbt.v21i3.3026
|View full text |Cite
|
Sign up to set email alerts
|

Ecological valuation of city parks (Case study for Mataram City)

Abstract: City parks, apart from having an aesthetic function as a place for recreation, also have an ecological function with vegetation components to soften the microclimate. Vegetation analysis was carried out in six city parks in Mataram City to determine the vegetation structure. Microclimate factors of the park, namely light intensity, air temperature and humidity inside and outside the park during the day and observations of sound attenuation at night have been carried out. Climatic data is carried out to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
2
2
0
Order By: Relevance
“…. This supports the results of a study conducted by Suripto et al (2021), who concluded that the variation in the ability of urban parks to soften the microclimate was not significantly related to variations in vegetation structure but was caused by variations in green area. It is also concluded that the low level of ability of urban parks to soften the microclimate is caused more by the lack of green area (less than 40%) in the park.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…. This supports the results of a study conducted by Suripto et al (2021), who concluded that the variation in the ability of urban parks to soften the microclimate was not significantly related to variations in vegetation structure but was caused by variations in green area. It is also concluded that the low level of ability of urban parks to soften the microclimate is caused more by the lack of green area (less than 40%) in the park.…”
Section: Resultssupporting
confidence: 90%
“…The results of this study strengthen the conclusions of previous research conducted by Suripto et al (2021), namely city gardens in Mataram City with varied vegetation structures but have the same level of ability (low level) in softening the microclimate. They also added that although the vegetation structure affects the park's ability to soften the microclimate, it turns out that the low ability of urban parks in Mataram City to soften the microclimate is caused more by the low portion of green area (vegetated land) in the park than the total park area.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations